A narrative-based approach to understand the impact of COVID-19 on the mental health of stranded immigrants in four border cities in Mexico - Cruz Piñeiro, Rodolfo; Ibarra, Carlos S. (Frontiers in Public Health, 2022)
Objective: This paper describes the impact that the different COVID-19 related restrictions have had on the mental health and well-being of 57 Central American and Caribbean immigrants stranded in Mexico due to the pandemic. Methods: Ethnographic data was obtained through the application of in-depth interviews centered on topics such as migration history, personal experience with COVID-19 and beliefs about the pandemic. This information was further analyzed through a narrative approach and Atlas Ti. Main findings: US Title 42 and the Migrant Protection Protocols (MPP) have stranded thousands of individuals in the US-Mexico border region, a situation that has overcrowded the available shelters in the area and forced many of the immigrants to live on the streets and in improvised encampments. Thus exposing them to a higher risk of contagion. Furthermore, the majority of the interviewed Central American and Caribbean immigrants consider that Mexico is more lenient when it comes to the enforcement of sanitary measures, especially when compared to their countries of origin. Finally, vaccination hesitancy was low among the interviewees, mainly due to the operative aspects of the vaccination effort in Mexico and the fear of ruining their chances to attain asylum in the US. These findings are backed up by the discovery of five recurring narratives among the interviewees regarding: 1) The pandemic’s psychological impact. 2) The uncertainty of being stranded in Mexico and the long wait. 3) Their fear of violence over the fear of contagion. 4) The perceived leniency of Mexico with the pandemic when compared to their countries of origin, and 5) Their beliefs about the pandemic and vaccines. Key finding: The mental health of stranded Central American and Caribbean immigrants in Mexico during the COVID-19 pandemic is mostly affected by their inability to make it across the US-Mexico border using legal means.